1985
DOI: 10.1039/c39850001568
|View full text |Cite
|
Sign up to set email alerts
|

Biosynthesis of nonactin. The role of acetoacetyl-CoA in the formation nonactic acid

Abstract: The incorporation of ethyl [I ,2,3,4-13C& and ethyl [I ,3-13C2]-acetoacetate into nonactic acid in cultures of Streptomyces griseus revealed the incorporation of several C2 units derived from acetyl-CoA, as well as a single intact C3 unit at C(l)-C(2)-C(lO).The carbon skeleton of nonactin (1) is assembled in Streptomyces griseus from two units of acetyl-CoA, one of succinyl-CoA, and one of propionyl-CoA, as revealed by 13C labelling experiments.1J The familiar concept of a 'starter unit' is, however, obscure i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
20
0

Year Published

1989
1989
2001
2001

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(20 citation statements)
references
References 0 publications
0
20
0
Order By: Relevance
“…The utilization of hexanoate in the biosynthesis of the fungal metabolite averufin, therefore, was an important experimental step forward in the understanding of polyketide biosynthesis. Report of these results (1, 2) was soon followed by the incorporation of acetoacetate into nonactin (13) and octanoate into the chain-terminating unit of fungichromin (14). Successes, however, were limited.…”
Section: Ef 'mentioning
confidence: 99%
See 1 more Smart Citation
“…The utilization of hexanoate in the biosynthesis of the fungal metabolite averufin, therefore, was an important experimental step forward in the understanding of polyketide biosynthesis. Report of these results (1, 2) was soon followed by the incorporation of acetoacetate into nonactin (13) and octanoate into the chain-terminating unit of fungichromin (14). Successes, however, were limited.…”
Section: Ef 'mentioning
confidence: 99%
“…The mixed anhydride method of Kass and Brock (21) using freshly prepared N-acetylcysteamine (22) gave the NAC thioesters of [1][2][3][4][5][6][7][8][9][10][11][12][13]butyric acid and [~-~~~] h e x a n o i c acid in 70-80% ields. This approach is summarized in Scheme 2.…”
Section: Ef 'mentioning
confidence: 99%
“…The biosynthesis of NON has been extensively studied by in vivo feeding experiments with 13 C-, 2 H-, and 18 O-labeled precursors and biosynthetic intermediates (2-5, 13, 45) and by isolation of both enantiomers of NA and the dimeric NA (17). These results established unambiguously the polyketide origin of NON, the assembly of which from one molecule each of propionate and succinate and two molecules of acetate must have invoked (i) the rare use of succinate as an intact fourcarbon fragment (C-3 to C-6) and (ii) the derivation of a three-carbon unit (C-7 to C-9) from two molecules of acetate (one of which is activated in the form of malonate) (Fig.…”
mentioning
confidence: 99%
“…2). Feeding experiments with 13 C-and 18 O-doubly-labeled precursors indicated that the C-3-O bond is formed during closure of the tetrahydrofuran ring, presumably by an intramolecular Michael addition of the 6-hydroxy group onto the enone moiety of 2-methyl-6,8-dihydroxynon-2E-enoic acid (NEA) (3,4). The involvement of the latter step in NON biosynthesis was further substantiated by the efficient and enantiospecific incorporation of both (6R,8R)-NEA into NON (45) and by the drastic reduction of NON production upon the addition of an NEA analog into the fermentation medium, which presumably acts as a suicide inhibitor for this enzymatic step (39).…”
mentioning
confidence: 99%
“…31–33 The biosynthesis of macrotetrolides has been studied extensively by in vivo feeding experiments with 13 C‐, 2 H‐, and 18 O‐labeled precursors and biosynthetic intermediates in Streptomyces griseus DSM40695 (also known as ETHA7796). The pioneer studies carried out by Robinson and co‐workers34–38 established unambiguously the polyketide origin of the macrotetrolides. As exemplified by 1 , the monomer for nonactin ( 2 ), the parent member of the family, its carbon backbone is assembled from one molecule each of propionate and succinate and two molecules of acetate (Fig.…”
Section: In Vivo Feeding Experiments: Macrotetrolides Are Of Polyketimentioning
confidence: 98%